2007
DOI: 10.1007/s10551-007-9350-3
|View full text |Cite
|
Sign up to set email alerts
|

Fairness, Feelings, and Ethical Decision- Making: Consequences of Violating Community Standards of Fairness

Abstract: unethical behavior, fairness, deception, emotions, community standards, justification,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(102 citation statements)
references
References 42 publications
5
96
0
1
Order By: Relevance
“…When individuals misplace their trust in others, they become vulnerable and are more likely to be exploited. Scholars have identified a number of psychological factors that influence unethical behavior (Gaspar & Schweitzer, 2013;Gino & Bazerman, 2009;Gino, Norton, & Ariely, 2010;Gino & Pierce, 2009;Gino, Schweitzer, Mead, & Ariely, 2011;Mead, Baumeister, Gino, Schweitzer, & Ariely, 2009;Moran & Schweitzer, 2008;Ordóñez, Schweitzer, Galinsky, & Bazerman, 2009;Ruedy & Schweitzer, 2010;Schweitzer, DeChurch, & Gibson, 2005;Schweitzer & Gibson, 2008;Schweitzer, Ordóñez, & Douma, 2004;Wiltermuth, Newman, & Raj, 2015). However, this rich literature has overlooked the critical role of trust in enabling unethical behavior.…”
Section: How Trust Enables Unethical Behaviormentioning
confidence: 99%
“…When individuals misplace their trust in others, they become vulnerable and are more likely to be exploited. Scholars have identified a number of psychological factors that influence unethical behavior (Gaspar & Schweitzer, 2013;Gino & Bazerman, 2009;Gino, Norton, & Ariely, 2010;Gino & Pierce, 2009;Gino, Schweitzer, Mead, & Ariely, 2011;Mead, Baumeister, Gino, Schweitzer, & Ariely, 2009;Moran & Schweitzer, 2008;Ordóñez, Schweitzer, Galinsky, & Bazerman, 2009;Ruedy & Schweitzer, 2010;Schweitzer, DeChurch, & Gibson, 2005;Schweitzer & Gibson, 2008;Schweitzer, Ordóñez, & Douma, 2004;Wiltermuth, Newman, & Raj, 2015). However, this rich literature has overlooked the critical role of trust in enabling unethical behavior.…”
Section: How Trust Enables Unethical Behaviormentioning
confidence: 99%
“…This may be especially important in teaching ethics to accounting students, as emotions have a direct impact on the process of ethical decision making (Schweitzer and Gibson, 2008;Connelly et al, 2004). Increased cognitive ethical development does not necessarily translate into increased ethical intentions, and the moderating variable may be emotions (Thorne, 2001; Gaudine and Thorne, 2001;Henrik 2008).…”
Section: Affective Objectivesmentioning
confidence: 99%
“…In addition, this behaviour was found to provide significant psychological benefits to the perpetrator including greater satisfaction and happiness, and reduced anger. Schweitzer and Gibson (2008) also found that perceptions of justifiability mediated the relationship.…”
Section: Implications For Theory Developmentmentioning
confidence: 85%
“…There is also a need to further explore the concept of justice and how different factors impact on subjective assessments of justice and motivate people to take action. As noted in this thesis, judgements of fairness have been found to have major implications for social systems (Schweitzer & Gibson, 2008). Perceived violations of fairness provoke reactions such as increased absenteeism (Hulin, 1991), stealing, and vandalism (Folger, 1993;Greenberg, 1990Greenberg, , 1993.…”
Section: Further Researchmentioning
confidence: 94%
See 1 more Smart Citation